O parecer de auditoria como instrumento de evidenciação: um estudo de caso - Wiesner, Wilmar (1987)
The objective of this paper is to explore the existing relation between the literature about qualified reports and the main report models used, by analysing the importance of the" latter for those who utilize accounting statements to make decisions (chapter I). Orr the review of the literature, the importance of accounting clarification as a whole is made clear and more precisely, the auditors counsel being an additional assurance for users (chapter 11). Then, the methodology applied for the unfolding of the research is shown, justifying the reasons for its usage in this kind of (chapter 111). An in-depth analysis of the available files at the de Valores Mobiliários made possible an account of the major that come to pass at the reports issued in Brazil, as 'well assessment of that Commission's performance regarding such (chapter IV). The results attained propitiated an analysis ~f the main existing problems regarding the qualified reports issued in Bra7.il, as well as the Comissão de Valores Mobiliários performance, aiming at improving the level of corporate accounting information (chapter V). Finally, relating the results to the existing literature, we were able to come to important conclusions and suggest new surveys in this area (chapter VI).